The Impact Of Resilience Skills And Teamwork Efficiency On Individual Work Performance With The Mediation Of Work Engagement In Emergency Installation Doctors In Banten Province, Indonesia - Heriyanto, Rivaldo Steven (Green Publisher Indonesia, 2025)
The purpose of this study is to know if status consumption gives positive effect to the seven of CSI’s shopping style characteristics. This study is applied in Jakarta using 250 millennial male consumers. Data are collected using 27 items questionnaires that measured with 1-5 Likert Scale and distributed with judgmental sampling method. SEM method on PLS system is used to analyze the data. The study result suggest that those millennial male consumers who are motivated to consume for status will utilize the shopping styles of being perfectionist/ high quality, brand conscious, novelty/ fashion conscious, impulsive/careless, recreational/ shopping conscious, and habitual/ brand loyal shopping style.